Technology Entrepreneurship Project (ENT 600) : Sony Corporation / Muhammad Zayyanie Ibnuataillah - Ibnuataillah, Muhammad Zayyanie (2021)
This project is an attempt to know how the theories can be applied to a practical situation. As a student in UiTM Arau, it is a part of a learning for everybody to perform a case study project. So, for this purpose, I got the opportunity to do a research on company which manufactured the same product that I want to develop, which is Sony Corporation Sony Corporation) is a Japanese multinational conglomerate corporation headquartered in Kōnan, Minato, Tokyo. The company operates as one of the world's largest manufacturers of consumer and professional electronic products, the largest video game console company, the second largest video game publisher, the second largest record company, as well as one of the most comprehensive media companies, being the largest Japanese media conglomerate by size overtaking the privately held, family-owned Yomiuri Shimbun Holdings, the largest Japanese media conglomerate by revenue. One of their focused products is the Sony Walkman In the first part of the study, I found that several problems that slowed down the business of Sony Walkman. My focused is on Sony A100 Walkman® A Series. Those problem are the display screen is fragile and the battery can only hold on for a minimum of 15 hours At the end of the study, I performed a SWOT analysis to detect this kind of problems. I recommend Sony to produce a casing made out of tempered glass in order to keep the Sony A100 Walkman® A Series save not only the display but also the whole body. I also recommend Sony to produce a Solar Charging Casing where the casing can charge the Walkman using the solar source in order to save time charging and increase the lasting of the Walkman battery.